Compensation Management In International Human Resource Management: Analyzing the Impact of Compensation Management on Organizational Health in MNCs (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this paper we discussed about one of the keycomponents of IHRM is the compensation administration in MNCs. Today,compensation and employee benefits contribute to the total costs. Compensationis strategically reported and monitored at the broad – levels and with theinvestors to assess the health of the organization.